PROMOTING LIVE WORKSHEETS TO RAISE SENIOR HIGH STUDENTS’ SPEAKING CONFIDENCE AND MOTIVATION - Teresa, Amelia; Febria, Desty (Dialectical Literature and Educational Journal, 2023)
Based on observations made in one of many existing senior high specialized government schools specifically in SMAN 20 Batam where English is a compulsory subject, the writer found that speaking motivation and confidence is still lacking, as well as a lack of technology exploration. By combining technology and face-to-face instruction, the method of blended learning (BL) used in this study utilizes Classroom Action Research (CAR) method. In addition to the pre-test and scoring rubric of the CAR cycle, Live Worksheet is provided as a breakthrough to solve the shortcoming by executing the online interactive platform as a post-test (final evaluation). As a result, of the Live Worksheet implementation of the blended learning CAR method, 90% of students of a representative 10th senior grade class have increased their speaking motivation and confidence, with 3 out of 5 speaking skill elements such as grammar structures, fluency, and pronunciation showing improvement skyrocketed to 80 points, contrast to the low pre-test result of 60 points for each element.